Evaluation of Cloud Computing Technology in Supporting Distributed Information Systems - Cynthia, Eka Pandu; Cynthia, Maulidania Mediawati; Cynthia, Dessy Nia (Journal of Electrical Engineering Research, 2025)
The rapid growth of distributed information systems has increased the demand for computing infrastructures that are scalable, reliable, and cost-efficient. Cloud computing has emerged as a prominent technological solution capable of addressing these demands by providing on-demand access to configurable computing resources. This study aims to evaluate the effectiveness of cloud computing technology in supporting distributed information systems by examining its capabilities, benefits, and inherent challenges. The research adopts a qualitative descriptive approach based on a systematic review and analysis of relevant academic literature, technical reports, and authoritative industry sources. The evaluation is conducted across several key dimensions, including scalability, availability and reliability, performance efficiency, security and data management, cost effectiveness, and system integration. The results indicate that cloud computing significantly enhances the operational performance of distributed information systems through elastic resource provisioning, fault tolerance mechanisms, and flexible pricing models. Cloud-based architectures also support improved interoperability and system integration through standardized interfaces and service-oriented designs. However, the findings reveal that challenges related to network latency, data privacy, regulatory compliance, and vendor dependency remain critical issues that must be carefully managed. Overall, this study concludes that cloud computing serves as a strong technological foundation for distributed information systems, provided that appropriate architectural designs, governance strategies, and resource management practices are implemented. The results contribute to a deeper understanding of cloud computing adoption and provide practical insights for organizations and system designers seeking to optimize distributed information system performance.